Bone marrow derived cells in adult skeletal muscle tissue in humans - Strömberg, Anna (BioMed Central, 2013)
BACKGROUND: During the past decade, several animal studies have demonstrated that in addition to local cells, cells from the bone marrow (BM) possess the ability to contribute to regeneration of injured skeletal muscle tissue. In addition, in mice, regular physical activity has been displayed to be a sufficient stimulus for BM-derived cell contribution to the muscle, indicating that this is part of the ongoing physiological remodeling of skeletal muscle. However, whether BM-derived cells participate in human skeletal muscle remodeling is not known. To this end, we analyzed the incorporation of BM-derived cells in healthy human skeletal muscle in women transplanted with male BM. METHODS: Skeletal muscle biopsies were obtained from the m. vastus lateralis of women transplanted with male donor hematopoietic stem cells 6 to 12 years earlier. Healthy women served as controls. Immunohistochemical staining for skeletal muscle fibers, satellite cells (SCs) or endothelial cells (ECs) combined with fluorescent in situ hybridization (FISH) of X and Y chromosomes was used to identify cells of BM origin within the biopsies. Three dimensional confocal imaging was performed to demonstrate colocalization of Y chromosome and DAPI within muscle fibers. To further investigate whether BM-derived cells incorporate into the SC niche, myoblasts were extracted from the biopsies from the transplanted women, cultured, and analyzed using XY FISH and immunocytochemistry. RESULTS: Three dimensional confocal imaging indisputably demonstrated colocalization of Y chromosome and DAPI within muscle fibers. Some Y chromosomes were found within centrally located nuclei. No Y chromosomes were detected in CD56+ SCs in the tissue sections nor in the myoblasts cultured from the extracted SCs. Y chromosome+ ECs were found in all sections from the transplanted subjects. No Y chromosomes were found in the skeletal muscle biopsies obtained from healthy control women. CONCLUSIONS: We demonstrate that BM-derived cells contribute to skeletal muscle fibers and ECs. Our results support that BM contribution to skeletal muscle occurs via direct fusion to muscle fibers, and that the contributing cells derive from the hematopoietic lineage. Thus, the present findings encourage further studies of the importance of this process for the physiological adaptation occurring throughout life.